1985
DOI: 10.2307/1130189
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Aggression: The Influence of Gender Label on the Perception of Aggression in Children

Abstract: To investigate the influence of gender label on adults' perceptions of aggression in children, a videotape of 2 preschool children playing roughly in the snow was shown to 175 college students (139 females, 36 males) who were asked to judge the degree of aggression displayed by 1 of the children (the target child). In the videotape, the children's snowsuits disguised their actual gender, and 4 experimental conditions were created by varying the gender label of both the target and the other (nonrated) child. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 40 publications
3
69
1
Order By: Relevance
“…Across conditions, the dyads were labeled as male-male, female-female, or male-female. They found that boy-boy interactions were rated as less aggressive and more playful than girl-boy and girl-girl interactions (Condry et al 1985). The authors speculated that this was due to the fact that play-fighting is a stereotypical play activity for boys, but not for girls; thus, boys were interpreted as having benign intentions, and girls were interpreted as having harmful ones.…”
Section: Introductionmentioning
confidence: 99%
“…Across conditions, the dyads were labeled as male-male, female-female, or male-female. They found that boy-boy interactions were rated as less aggressive and more playful than girl-boy and girl-girl interactions (Condry et al 1985). The authors speculated that this was due to the fact that play-fighting is a stereotypical play activity for boys, but not for girls; thus, boys were interpreted as having benign intentions, and girls were interpreted as having harmful ones.…”
Section: Introductionmentioning
confidence: 99%
“…It was predicted that when the aggressor was a male, the participants would predict that he would use direct aggression (physical and verbal) more than when the aggressor was a female; the results confirmed this. Since previous research supports the view that indirect aggression is more typical of females [1,26,[28][29][30][31][32][33][35][36][37][38][39], and more experience with a certain behavior will enhance stereotypical beliefs between sex differences in aggressive behavior [43], it was predicted that females would be predicted to use indirect aggression more often than males, and as expected, results confirm this hypothesis; when the aggressor was a female, the adolescents predicted that the aggressor would use indirect aggression more than when the aggressor was a male.…”
Section: Discussionmentioning
confidence: 98%
“…In some of these studies the results indicated that when the sex was unknown, the subjects viewed the aggression between two boys as the least aggressive, as their behavior was more likely to be attributed to rough-and-tumble play than to intentional harm. However, the subjects viewed such behavior by girls as aggression rather than as play [43]. On the other hand, in similar studies the sex of the children was made clear to observers, and when the sex of the aggressor and the target was known, subjects rated boys and girls as equally aggressive; neverthe-less, boys' aggression was seen as more intentional and masculine [44,45].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, it is also the case that environmental factors are also influential in explaining aggression. Aggressive behavior in both boys and girls has been found to be related to features of child-rearing, including harsh parental discipline and physical punishment, as well as to sex-differentiated reactions to aggressive acts by children on the part of parents and other adults (parke & Slaby, 1983;Condry & Ross, 1985). Exposure to televised violence has been associated with aggressive behavior in children (Bandura, Ross, & Ross, 1961) and extended exposure to violent television during childhood is associated with aggressive behavior in adolescence (Eron & Huesmann, 1980).…”
Section: Sex-role Socialization During Middle Childhood and Adolescencementioning
confidence: 99%